2021
DOI: 10.1021/acs.langmuir.0c02652
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of Seven Different Classes of Antibiotics into LPS Monolayers Supports Three Different Permeation Mechanisms through the Outer Bacterial Membrane

Abstract: The outer membrane (OM) of Gram-negative (G−) bacteria presents a barrier for many classes of antibacterial agents. Lipopolysaccharide (LPS), present in the outer leaflet of the OM, is stabilized by divalent cations and is considered to be the major impediment for antibacterial agent permeation. However, the actual affinities of major antibiotic classes toward LPS have not yet been determined. In the present work, we use Langmuir monolayers formed from E. coli Re and Rd types of LPS to record pressure–area iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 77 publications
1
22
0
Order By: Relevance
“…Indocyanine green [144,170] Potential anticancer drug Curcumin [164,[227][228][229], Aplysiatoxin [230], Bryostatin [231], Phorbol [231], 12,13-dibutyrate [231], Prostratin [231] Antibiotics Imipenem [232], Doripenem [232], Ertapenem [232], Meropenem [232], Ciprofloxacin [233,234], Ciprofloxacin ternary copper complex [235], Daunorubicin [209], Idarubicin [209],…”
Section: Application and Target Drugs And Pharmaceuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indocyanine green [144,170] Potential anticancer drug Curcumin [164,[227][228][229], Aplysiatoxin [230], Bryostatin [231], Phorbol [231], 12,13-dibutyrate [231], Prostratin [231] Antibiotics Imipenem [232], Doripenem [232], Ertapenem [232], Meropenem [232], Ciprofloxacin [233,234], Ciprofloxacin ternary copper complex [235], Daunorubicin [209], Idarubicin [209],…”
Section: Application and Target Drugs And Pharmaceuticsmentioning
confidence: 99%
“…Levofloxacin [236][237][238], Clarithromycin [236], Isoniazid N -acylated derivatives [239], Rifampicin [234,240], Mangostin [241], Trimethoprim [242], Negamycin [243] Potential antibiotic Kanamycin A [133], nTZDpa and its derivatives [244], Cholic acid derived amphiphiles [245], γ-terpineol [246], Bithionol [247] Antimicrobial compound Chlorhexidine [248][249][250], Triclosan [251], Octenidine [250] Antiparasitic Praziquantel [252] Antiviral drugs Darunavir [253], Amantadine [254][255][256], Spiro[pyrrolidine-2,2 -adamantane] [254,255], 20,30-dideoxyadenosine (Didanosine) [242], Saffron [257] Antifungal drug Itraconazole, [184,186,187,258], Nystatin [259], Amphotericin B [260] Rheumatoid arthritis Lapatinib [213] Nonsteroidal antiinflammatory drugs, inhibitor of cyclooxygenase-1 and -2…”
Section: Application and Target Drugs And Pharmaceuticsmentioning
confidence: 99%
“…The controlled density of monolayer packing provides the antibiotic molecules access to all parts of lipid molecules through a range of compression states and also allows estimation of the molecular insertion area. Cethuk et al [116] have applied the Langmuir monolayer method to confirm that the structure of the antibiotic has a significant impact on the incorporation mechanism of the compound in the model membrane. They have revealed that the hydrophobicity of the antibiotic is a desirable feature which helps in its insertion and retention inside the aliphatic slab of LPS over a range of pressures.…”
Section: Modelling Of Cellular Membrane For Antibiotic Biodegradation Studiesmentioning
confidence: 99%
“…The measurements using the Langmuir technique have also confirmed that the polar/electrostatic mode is obviously more disruptive for the LPS layer, which explains why aminoglycosides and polymyxins are more effective and specific against Gram-negative bacteria. Moreover, based on the data obtained with the Langmuir technique, the authors of [116] have proposed some simple criteria to predict which compounds will cross the membrane. It has been suggested that if an antibiotic can hold a detectable mole fraction among LPS molecules during compression all the way to reach the collapse pressure, then it can be expected that this drug would likely permeate through the native bacterial membrane.…”
Section: Modelling Of Cellular Membrane For Antibiotic Biodegradation Studiesmentioning
confidence: 99%
“…Colistin, or polymyxin E, is a cationic lipopeptide and “last-resort” antibiotic used for MDR Gram-negative infections, such as those producing extended-spectrum beta-lactamases and those resistant to carbapenems ( 6 ), which is an increasing concern in clinical isolates of Enterobacter species ( 7 ). Targeting the cell membrane, cationic colistin binds with anionic lipopolysaccharide (LPS) through electrostatic interactions ( 8 11 ). Colistin resistance is conferred by reduction of the electronegativity of the cell membrane through modification of the terminal phosphate residues of lipid A, the membrane anchor of LPS, thereby decreasing the binding affinity of colistin ( 12 ).…”
Section: Introductionmentioning
confidence: 99%